POLITICAL RISK IN FOREIGN DIRECT INVESTMENT IN THE RUSSIAN ELECTRIC POWER SECTOR - Haaraoja, Miia (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Russia approved ambitious reform plan for the electricity sector in 2001 including privatisation of the country’s huge thermal generation assets. So far the sector had suffered from power shortages, aging infrastructure, substantial electricity losses, and weak productivity and profitability numbers. There was obvious need for foreign investments and technologies. The reform was rather successful; the generation assets were privatised in auctions in 2007-2008 and three European energy companies, E.On, Enel and Fortum, invested in and obtained together over 10% of the Russian production assets. The novelty of these foreign investments serves unique object for the study. The political risk is involved in the FDI due to the industry’s social and economic importance. The research’s objective was to identify and analyse the political risk that foreign investors face in the Russian electricity sector. The research had qualitative study method and the empirical data was collected by interviewing. The research’s theoretical framework was based on the existing political risk theories and it focused to understand the Russian government in relation to the country’s stability and define both macro-level and micro-level sources of political risk for the foreign direct investments in the sector. The research concludes that the centralised and obscure political decision-making, economic constriction, high level of governmental control in economy and corruption form the country’s internal macro-level risk sources for the foreign investors in the sector. Additionally the retribution due to the companies’ home country actions, possible violent confrontations at the Russian borders and the currency instability are externally originated risk sources. In the electricity industry there is risk of tightened governmental control and increased regulation and taxation. Similarly the company-level risk sources link to the unreformed heating sector, bargaining with the authorities, diplomatic stress between host and home countries and to companies and government’s divergent perspective for the profit-making. The research stresses the foreign companies’ ability to cope with the characteristics of Russian political environment. In addition to frequent political and market risk assessment, the companies need to focus on currency protection against rouble’s rate fluctuation and actively build good company-citizenship in the country. Good relationship is needed with the Russian political authorities. The political risk identification and the research’s conclusive framework also enable political risk study assessments for other industries in Russia

Vuonna 2001 Venäjä hyväksyi kunnianhimoisen sähkösektorin uudistusohjelman, johon kuului maan valtavan fossiilisen sähköntuotannon yksityistäminen. Toimiala olikin kärsinyt sähkökatkoksista, vanhenevasta rakenteesta, huomattavasta hävikistä sekä heikoista tuottavuus- ja kannattavuusluvuista. Ulkomaisille investoinneille ja tekniikoille oli selkeä tarve. Uudistus onnistui suhteellisen hyvin: tuotantolaitokset yksityistettiin huutokaupoissa vuosina 2007-2008 ja kolme eurooppalaista energiayhtiötä, E.On, Enel ja Fortum, investoivat toimialalle ja ottivat haltuunsa yli 10 % Venäjän sähköntuotantokapasiteetista. Ko. ulkomaisten investointien uutuus tarjoaa ainutlaatuisen tutkimuskohteen. Investointeihin liittyy poliittinen riski johtuen alan yhteiskunnallisesta ja taloudellisesta merkityksestä. Tutkimuksen tarkoitus oli tunnistaa ja analysoida millaisen polittiisen riskin ulkomainen investoija kohtaa Venäjän sähkötoimialalla. Tutkimusmenetelmä oli laadullinen ja tutkimuksen aineisto kerättiin haastattelemalla. Tutkimuksen teoreettinen viitekehys perustui olemassa oleviin poliittisen riskin teorioihin ja sen avulla oli tarkoitus ymmärtää Venäjän nykyjohdon merkitys maan vakaudelle sekä määrittää suorien ulkomaisten investointien poliittisen riskin tekijät sekä makro- että toimialatasolla. Tutkimuksen johtopäätös on, että keskittynyt ja epäselvä poliittinen päätöksenteko, talouden supistuminen, hallituksen sekaantuminen talouteen sekä korruptio muodostavat maan sisäisiä makrotason poliittisia riskitekijöitä ulkomaisille investoijille sähkötoimialalla. Lisäksi maan ulkopuolelta aiheutuvat kostotoimet liittyen yritysten kotimaiden toimintaan, mahdolliset väkivaltaiset yhteenotot Venäjän rajoilla sekä valuuttakurssin vaihtelut ovat riskitekijöitä. Itse sähkösektorilla riskitekijöinä ovat kiristyvä valtion kontrolli sekä lisääntyvä sääntely ja verotus. Samanaikaisesti yritystason riskitekijät liittyvät uudistamattomaan lämpösektoriin, neuvottelumahdollisuuksiin päättäjien kanssa, kitkaan maiden välisissä diplomaattisissa suhteissa sekä yritysten ja Venäjän erilaisiin näkemyksiin tuloksenteosta. Tutkimus painottaa yritysten kykyä luovia Venäjän poliittisessa ympäristössä. Jatkuvan poliittisen riskin sekä markkinariskin arvioinnin lisäksi yritysten tulee huomioida valuutan suojaaminen ruplan kurssiheilahteluja vastaan sekä aktiivisesti rakentaa hyvää yrityskansalaisuutta maassa. Venäjän poliittisiin päättäjiin tarvitaan hyvät suhteet. Poliittisen riskin tunnistaminen ja tutkimuksen lopullinen viitekehys mahdollistavat poliittisen riskin tutkimuksen myös jollakin toisella toimialalla Venäjällä.